Identifikasi Proses Produksi Komponen Guide dengan Metode DMAIC pada Supplier PT. X - Yunita, Neflin; Adi, Prayonne (Jurnal Titra, 2019)
This research was conducted to identify the cause of the problem the production process guide with DMAIC Method on supplier PT. X. background observation component of the guide is the result of stock opname with values above 50% difference compared to the other subcontracting materials. Stock Opname done inside to compare the actual data and systems. Difference between actual data and systems are referred to as variants. Variants can occur because system administration errors. The identification of the causes of the problems of the production process guide done by field visits to supplier. The identification effort shows there are problems other than the administration of the system. The problem is the wrong guide, send reject materials, results of cut less than standard. The methods used in analyzing these problems is the method Define, Measure, Analyze, Improve, Control (DMAIC). The results of the analysis into a reference making checksheet rejects daily, work instruction, inspection jig, instructon material, and stopper for each process in the troubled supplier. The results of the implementation is any problem declining. Stock opname period July 2018 is 2010.97 kg during the period December 2018 declined be 1033.91 kg.